A Seismic‐Frequency Laboratory Study of Solid Substitution in Bentheim Sandstone. Issue 6 (20th June 2019) - Mikhaltsevitch, V.; Lebedev, M.; Gurevich, B.; Sun, Y.; Glubokovskikh, S.
Abstract: Studying the effects of the solid pore fills on the elastic properties of rocks is of significant importance for a range of applications, such as, for example, monitoring of heavy oil reservoirs or modeling the transport properties of the rocks affected by salt precipitation or cementation. We present the results of the laboratory solid‐substitution experiments carried out on Bentheim sandstone at a seismic frequency of 2 Hz. The experiments were performed when the pore space of the tested sample was filled sequentially with solid (23°C) and liquid (40°C) octadecane. Previously, ultrasonic measurements on the same octadecane‐filled sandstone showed significant discrepancy from the predictions of Ciz‐Shapiro theory, which was explained by the effect of stiffening of compliant pores at the grain contacts. However, the present results show good agreement with the predictions of the Ciz‐Shapiro theory and suggest that the effect of stiffening of the compliant pores in presence of solid is negligible at low frequency. Key Points: Laboratory measurements of the elastic moduli of a sandstone sample filled with solid octadecane are conducted at seismic frequency The measured drained moduli of the sample are verified using the Gassmann theory The low‐frequency experimental results corroborate the predictions of the Ciz‐Shapiro theory